PENGARUH GREEN TALENT MANAGEMENT (GTM) TERHADAP PERILAKU KERJA INOVATIF DIMEDIASI PEMBERDAYAAN PSIKOLOGIS PADA KARYAWAN PT HINDOLI (A CARGILL COMPANY) - Fitriyani, Ayu; Muafi (JURNAL MANAJEMEN DAKWAH, 2024)
This study aims to test and analyze the effect of Green Talent Management (GTM) such as Green Soft TM and Green Hard TM on innovative work behavior mediated by psychological empowerment. This study used 150 samples taken from employees of PT Hindoli Mill Sungai Lilin (a cargil company). The data analysis used in this study used the Structural Equation Model (SEM) method, namely Partial Least Square (PLS) with SamrtPLS 4.0 software. The results obtained in this study indicate that: (1) Green Soft TM has no positive effect on innovative work behavior, (2) Green hard TM has a positive effect on innovative work behavior, (3) Psychological empowerment has a positive effect on innovative work behavior, (4) Green Soft TM has a positive effect on psychological empowerment, (5) Green Hard TM has a positive effect on psychological empowerment, (6) Green Soft TM has a positive effect on innovative work behavior mediated by psychological empowerment, (7) Green Hard TM has a positive effect on innovative work behavior mediated by psychological empowerment.